ANALYZING FACTORS OF IN-FLIGHT SERVICES OF GARUDA INDONESIA AND BATIK AIR TOWARDS PASSENGERS SATISFACTION - Tulandi, Victor Michael; Tumewu, Ferdinand (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Transportation services play an important role in supporting any activity, of human. Various types of the transportation that we use. Among them, are air transportation or airplane. Talk about the satisfaction of airline passenger, nowadays many airlines competing to provide the best service for the passengers, one of the things that can influence passenger satisfaction is through airline service especially in-flight service. The objective of this research is to identify the factors of in-flight services of Garuda Indonesia and Batik Air that influence passengers satisfaction. The method used in this research is quantitative method by spread out the questionnaire to get the primary data. The population of this research are people in the North Sulawesi in particular Bitung city who ever used the airline services especially Garuda Indonesia and Batik Air with sample as many as 99 respondents. The analysis techniques used to analyze the data is exploratory factor analysis. The results of this research found eight factors, those factors are: in-flight physical environmental, food and beverages, in-flight entertainment service, cabin crew service, in-flight seat comfort, in-flight shopping and aircraft, in-flight reading service, and in-flight safety demonstration. Garuda Indonesia and Batik Air should pay attention to in-flight services and should also seek information related to the desire of passengers so they can provide the best in-flight services for the passengers satisfaction. Keywords: in-flight services, passengers satisfaction